answer is hcbiurrcuiehdieuhideidehdue -12y+48
Multiplying both sides of an equation by the same number keeps the equation true. In this example, both sides are multiplied by 3, so the equation isn't changed.
The answer to you’re question is 5 1/2 multiplied by 5 1/3. I submitted a photo showing how to put the answer.
F(x) = (x² - 3x - 10)(x + 4) becomes (x - 5)(x + 2)(x + 4) when completely factored. Now set each binomial equal to zero.
x - 5 = 0
x = 5
x + 2 = 0
x = - 2
x + 4 = 0
x = - 4
Your zeros are at x = - 4, - 2, and 5. Or at (- 4, 0), (- 2, 0), and (5, 0).
The answer is Square pyramid